2020
DOI: 10.18522/2311-3103-2020-3-173-183
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Approach for Deep Learning Based Finger Vein Biometrics Template Security

Abstract: Мы живем в современном обществе, где у нас достаточно много ресурсов и вычислительной мощности, единственной проблемой остается общественная безопасность. С развитием технологий личная информация становится все более не защищенной. Поэтому идентификация личности является актуальной проблемой. Существующие традиционные методы защиты личной информации оказались не надежными. Защита биометрических параметров является одной из наиболее важных проблем при обеспечении безопасности современной биометрической системы.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…At the same time, the inhomogeneity image correction, which is one of the pre-processing steps, increased the accuracy by 2-3 percent. [16] aimed to show that personal or identical verification is a fundamental issue for providing authentication or security. The researchers found that biometric template protection is one of the most critical issues in securing today's biometric system through a hybrid method for finger vein biometric recognition based on a deep learning approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the inhomogeneity image correction, which is one of the pre-processing steps, increased the accuracy by 2-3 percent. [16] aimed to show that personal or identical verification is a fundamental issue for providing authentication or security. The researchers found that biometric template protection is one of the most critical issues in securing today's biometric system through a hybrid method for finger vein biometric recognition based on a deep learning approach.…”
Section: Literature Reviewmentioning
confidence: 99%